IL-37 Plays a Beneficial Role in Patients with Acute Coronary Syndrome - Mao, Xiaobo; Zhu, Ruirui; Zhang, Fangyuan; Zhong, Yucheng; Yu, Kunwu; Wei, Yuzhen; Sun, Haitao; Xu, Wenbin; Luo, Quan; Wang, Yue; Ding, Yan; Zeng, Qiutang (Mediators of Inflammation, 2019)
Background. Interleukin-37 (IL-37) acts as an inhibitor of innate and adaptive immunity. However, the exact role of IL-37 in the patients with acute coronary syndrome (ACS) remains to be elucidated. Methods. Patients were classified into 4 groups: normal coronary artery (NCA), stable angina (SA), unstable angina (UA), and acute myocardial infarction (AMI). The circulating Treg, Th1, and Th17 frequencies were measured. The effect of IL-37 on stimulated peripheral blood mononuclear cells (PBMCs) and the influence of IL-37 on DCs were explored. In addition, the role of IL-37-treated tDCs on Treg cell expansion and the stability of these tDCs were also tested. Results. Our results showed that the circulating Treg frequencies were decreased, while Th1 and Th17 frequencies were increased in ACS patients, and that IL-37 expanded Tregs but suppressed Th1 and Th17 cells in activated PBMCs derived from ACS patients. Of note, IL-37-treated human DCs obtained a tolerogenic phenotype, and such tDCs promoted expansion of Tregs and decreased the Th1 and Th17 populations when cocultured with CD4+ T cells. Interestingly, IL-37-treated DCs from patients with ACS are phenotypically and functionally comparable to IL-37-treated DCs from NCA patients, and tolerogenic properties of IL-37-treated DCs were highly stable. Conclusion. In conclusion, our results reveal a beneficial role of IL-37 in the patients with ACS and suggest that autologous IL-37-treated tDCs may be a novel therapeutic strategy for the patients with ACS.